Little‐v0 Agreement and Templatic Morphology in Ch'ol. (26th April 2017) - Coon, Jessica
Abstract: This paper addresses typological differences in subject–verb agreement and provides evidence that transitive subject agreement need not always involve a high functional head, namely T 0, but may instead be the result of a local relation between the subject and a low functional head, v 0 . In Mayan languages, grammatical relations are head‐marked on the predicate through two series of morphemes, known as "Set A" (ergative/possessive) and "Set B" (absolutive). I argue that Set A morphemes reflect a local relationship of agreement between v 0 and the transitive subject in its low base position and, in an analogous structural configuration in the nominal domain, between a possessive n 0 head and the possessor. Crucially, I show that no higher functional projection is involved. This is important in light of proposals that ergative agreement systems are epiphenomenal, resulting from standard nominative agreement from T 0 which is blocked from agreeing with morphologically case‐marked ergative subjects (Woolford2010 ). In this paper, I examine the morphologically ergative Mayan language Ch'ol to show that true ergative agreement is possible even in the absence of morphological case. This paper has implications for the typology of ergative case and agreement systems and contributes to our understanding of the nature of agreement and clitic doubling.